Termodinámica & forma: Relación entre los cuatro sólidos básicos, el material y el clima en el contexto Bogotá (2014)
To meet the requirements needed by the Faculty of Architecture for graduate qualification, we will conduct an inquiry about the thermodynamics field. The topic to be discussed in our degree project will be Shapes and Thermodynamics, in which we will identify which architectural shapes achieves in optimize the energy conservation according with the bioclimatic in buildings We will develop a second part of the research, which we will apply the results and conclusions of the first part in a healthy housing proposal, with form and materials that will generate the best energetic balance according to the results, developing and applying also bioclimatic in different locations or climatic zones of the country.